Vegetation and the terrestrial carbon cycle : modelling the first 400 million years - Beerling, D. J. (Cambridge University Press, 2001)
Using knowledge of present day vegetation processes and models of global climate, the authors simulate and analyse changes in the earth's vegetation and in the capacity of the Earth's carbon cycle over the past 400 million years. Possible conditions in future centuries are also investigated, providing valuable predictions.